Anxiety impact during COVID-19: a systematic review - Patricia Batista; Vitor Duque; Ana Luzio-Vaz; Anabela Pereira (Journal of Infection in Developing Countries)
Introduction: The COVID-19 epidemic has been causing serious physical, but also psychological effects in society. This systematic review sought to identify studies that describe COVID-19 related anxiety, and to understand the impact of anxiety assessment in defining strategies to be implemented in future studies.